2008
DOI: 10.1111/j.1743-6109.2008.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Low Sexual Function in Women: A Study of 1,009 Women in an Outpatient Clinic of a University Hospital in Istanbul

Abstract: Introduction Sexual functioning is a common and multidimensional problem, associated with multiple biological, medical, psychological, sociocultural, political, economic, and interpersonal factors. Aim The study was planned to determine the prevalence and risk factors for low sexual function in women in an outpatient clinic of a university hospital in Istanbul. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
129
6
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 33 publications
35
129
6
14
Order By: Relevance
“…Additionally, longer period since the diagnosis and presence of another chronic disorders are significantly predictive of poor sexual functioning. This is consistent with other studies conducted in Turkey, which also found a significantly higher prevalence of sexual dysfunction in the presence of older age, lower educational level, unemployment status (Aslan et al, 2008;Erenel and Kitiş, 2011;Akkuzu et al, 2014). In the literature, consistent with the findings of the current study, it is reported that a large proportion of patients with gynecologic cancers suffer sexual problems (Barton-Buckle and Gustason, Reis et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, longer period since the diagnosis and presence of another chronic disorders are significantly predictive of poor sexual functioning. This is consistent with other studies conducted in Turkey, which also found a significantly higher prevalence of sexual dysfunction in the presence of older age, lower educational level, unemployment status (Aslan et al, 2008;Erenel and Kitiş, 2011;Akkuzu et al, 2014). In the literature, consistent with the findings of the current study, it is reported that a large proportion of patients with gynecologic cancers suffer sexual problems (Barton-Buckle and Gustason, Reis et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…In Turkey, as in most cultures, many healthy women without any physical diagnosis or disease have sexual problems (Yılmaz and Eryılmaz, 2004;Reis et al, 2010;Erenel and Kitiş, 2011). Because Turkey is a traditional societ, sexual experience before marriage is unacceptable particularly for young women, and women often engage in sex so as to meet the requirements of men (Aslan et al, 2008;Erenel and Kitiş, 2011). There are studies showing that patients with satisfactory sexual lives before treatment tend to have satisfactory sexual lives after treatment and are able to successfully cope with the effects of the cancer treatment on their sexual life (Corney et al, 1993;Helstrom, 1994;Yılmaz and Eryılmaz, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resultados discordantes são encontrados na literatura 9,22,[25][26][27] , mostrando que essas doenças estariam associadas aos piores escores de sexualidade. Tais resultados discrepantes podem ser atribuídos às diferenças metodológicas encontradas quanto ao tipo de questionário empregado (Short Personal Experiences Questionnaire 9 e FSFI 20,22,[25][26][27] ), à característica da população incluída (escolaridade mínima de 11 anos 9 , mulheres chinesas 20,27 , mais de 20 anos 22 , 20 a 60 anos 27 , sem outras morbidades 27 , tipo de diabetes 26,27 ) e ao tipo de análise utilizada (regressão logística 20,27 ).…”
Section: Discussionunclassified